Circannual Growth in Wisconsin Children and Adolescents: Identifying Optimal Periods of Obesity Prevention - VanWormer, Jeffrey J. (Pediatr Obes, 2019)
BACKGROUND: Recent studies suggest kids tend to gain the most weight in summer, but schools are chastised for supporting obesogenic environments. Conclusions on circannual weight gain are hampered by infrequent body mass index (BMI) measurements, and guidance is limited on the optimal timeframe for pediatric weight interventions. OBJECTIVES: This study characterized circannual trends in BMI in Wisconsin children and adolescents, and identified sociodemographic differences in excess weight gain. METHODS: An observational study was used to pool data from 2010-2015 to examine circannual BMI z-score trends for Marshfield Clinic patients age 3-17 years. Daily 0.20, 0.50, and 0.80 quantiles of BMI z-score were estimated, stratified by gender, race, and age. RESULTS: BMI z-scores increased July-September, followed by a decrease in October-December, and another increase-decrease cycle beginning in February. For adolescents, the summer increase in BMI was greater among those in the upper BMI z-score quantile relative to those in the lower quantile (+0.15 units vs. +0.04 units). This pattern was opposite in children. CONCLUSIONS: BMI increased most rapidly in late summer. This growth persisted through autumn in adolescents who were larger, suggesting weight management support may be beneficial for kids who are overweight at the start of the school year.